The state of vascular surgery education in the United States - Lavanga, Elizabeth; Dogbe, Leana; Soucy, Jacob; Aziz, Faizaan; Nguyen, S. Lauren; Zil-E-Ali, Ahsan; Aziz, Faisal (Frontiers in Surgery, 2024)
With growing proportion of elderly population in the US and a relatively fixed supply of well-trained vascular surgeons, there is a serious concern that we will be facing a shortage of vascular surgery workforce in the near future(1). One of the main reasons why there is a shortage of vascular surgeons in the US is due to the fact that many students don't get exposed to this field throughout their student lives and a recent survey of medical students from a non-urban tertiary care academic institution showed that early exposure of the medical students to the surgical careers is correlated with an increased interest in the surgical field(2). This review of the state of vascular surgery education in the US at the undergraduate level describes in detail the importance of an early introduction to vascular surgery in the education curricula, the current state of the education, potential avenues to improve the exposure of students to the field of vascular surgery and the importance of this effort in matching the increasing need for vascular surgeons for an aging population which is likely to require dedicated care by vascular surgeons of the future. At the present time, the two pathways by the Accreditation Council for Graduate Medical Education (ACGME) to obtain dedicated vascular surgery training in the US include either enrolling in a two year clinical fellowship after completion of general surgery training or to match in a five year vascular surgery integrated residency program after successful completion of medical degree.The review is divided into the following sections: I.